2012
DOI: 10.1063/1.4773212
|View full text |Cite
|
Sign up to set email alerts
|

Germanium metal-semiconductor-metal photodetectors evanescently coupled with upper-level silicon oxynitride dielectric waveguides

Abstract: We demonstrate Ge-on-Si metal-semiconductor-metal (MSM) photodetectors monolithically integrated with silicon oxynitride (SiOxNy) waveguides. The waveguide is placed on top of the photodetector and between the metal electrodes, evading the shading effect by metal electrodes, which is typical in surface-illuminated MSM photodetectors. The devices showed responsivity of about 0.45 A/W for 80 μm long devices at 1550 nm. The photodetector with 1.5 μm electrode spacing showed 3 dB bandwidth of 2.0 GHz at −2 V and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As expected, the higher response to incident irradiation is demonstrated in Device D and E, instead of Device C. The higher photocurrents of Device D and E can be mainly attributed to their ultrahigh QD density and smaller lateral size despite the presence of other secondary factors such as carrier mobility, the metal-semiconductor interface state, and Schottky barrier height. Generally, the higher the QD density, the more the photogenerated carriers; and the smaller the QD lateral size, the less the bound carrier is scattered by the phonon [43][44][45]. According to Shi, the absolute responsivity R and internal quantum efficiency (IQE) in a typical MSM device can be expressed as R=I/P and η i =(I/q)/(P/hυ), respectively.…”
Section: I-v Characteristics Of Qdsmentioning
confidence: 99%
“…As expected, the higher response to incident irradiation is demonstrated in Device D and E, instead of Device C. The higher photocurrents of Device D and E can be mainly attributed to their ultrahigh QD density and smaller lateral size despite the presence of other secondary factors such as carrier mobility, the metal-semiconductor interface state, and Schottky barrier height. Generally, the higher the QD density, the more the photogenerated carriers; and the smaller the QD lateral size, the less the bound carrier is scattered by the phonon [43][44][45]. According to Shi, the absolute responsivity R and internal quantum efficiency (IQE) in a typical MSM device can be expressed as R=I/P and η i =(I/q)/(P/hυ), respectively.…”
Section: I-v Characteristics Of Qdsmentioning
confidence: 99%
“…It has recently been reported that a hollow-core photonic-band gap fiber yielded a record combination of low loss and wide bandwidth [4]. Beyond telecommunications waveguides are used in integrated optical circuits [5], and terabit chip-to-chip interconnects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Planar WGs with onedimensional (1D) confinement, such as a dielectric slab, and fiber WGs with two-dimensional (2D) confinement, are widely used, for example in fiber optic cables for telecommunication, photonic crystal fibers, 1 integrated optical circuits 2 , and terabit chip-to-chip interconnects. 3 The optical spectra of WGs, however, do not consist of only these bound modes called WG modes, but also contain unbound modes which couple to the outside, commonly known as leaky modes. An elegant and intuitive way to understand and describe the properties of optical systems is to use the concept of discrete resonant states 4,5 (RSs) which include all types of modes in the system and present a mathematically complete set of spatial functions.…”
Section: Introductionmentioning
confidence: 99%